Recycling treatment of carbon fibre/epoxy composites: Materials recovery and characterization and environmental impacts through life cycle assessment. (1st November 2016) - La Rosa, A.D.; Banatao, D.R.; Pastine, S.J.; Latteri, A.; Cicala, G.
Abstract: A new commercial amine-based epoxy curing agent, engineered to produce recyclable composites, was studied. Carbon fibre (CF)/epoxy composites were manufactured through high-pressure resin transfer moulding (HP-RTM) and chemically treated in order to recover clean CFs as well as an epoxy thermoplastic polymer, as recycled products. The chemical structure of the new epoxy thermoplastic polymer obtained was drawn and confirmed by polymer characterisation. Furthermore an evaluation of the avoided environmental impacts associated to the recyclability of the thermoset composite was carried out, by using the Life Cycle Assessment (LCA) method.